Ferrocenyl thiazolidine-2-thione ornamented 1D coordination polymers derived from coinage metal halides and pseudohalides. Issue 44 (29th October 2021) - Singh, Ayushi; Trivedi, Manoj; Kociok-Köhn, Gabriele; Singh, Ashish Kumar; Muddassir, Mohd.; Kumar, Abhinav
Abstract : Three new ferrocene-functionalized thiazolidine-2-thione coinage metal coordination polymers with halides and pseudo-halides were synthesized and the nature of their weak interactions was assessed. Abstract : Two new Cu(i ) and one Ag(i ) coordination polymer have been synthesized using a ferrocene-functionalized ligand, 3-ferrocenyl methyl-thiazolidine-2-thione (L). These polymers, composed of [CuCN(L)] n (FcCuCN ), [AgCN(L)] n (FcAgCN ) and [CuI(L)2 ] n · n CHCl3 (FcCuI ), have been characterized by FTIR, 1 H and 13 C NMR, solid-state UV-vis spectroscopy and single-crystal X-ray diffraction analysis. Single-crystal X-ray diffraction studies suggest that FcCuCN and FcAgCN are isostructural and the immediate coordination geometry around Cu(i ) and Ag(i ) is trigonal planar, which is satisfied by the exocyclic sulfur of L, one cyano nitrogen and one cyano carbon. On the other hand, FcCuI possesses two discrete monomeric L-Cu-I entities where a four-coordinate geometry around Cu(i ) is defined by two exocyclic sulfurs of two L ligands and two iodo groups. Structural differences between FcCuCN and FcCuI arise due to different pseudohalide and halide ligands bound to the Cu(i ) centers. The solid-state structures of these complexes have been stabilized by varied interactions out of which the most interesting interactions are the C–H⋯Cu and C–H⋯Ag anagostic interactions in FcCuCN and FcAgCN, respectively, and the Cu⋯Cu cuprophilic interaction in FcCuI . All these interactions and their nature as well as their percentage contribution have been studied by Hirshfeld surface analyses. The weak interaction energies existing in all the three polymers have been assessed with the help of density functional theory (DFT) and quantum theory of atoms in molecules (QTAIM). Mayer bond order and Wieberg bond indices have also been calculated. Additional band gap calculations suggested that the isostructural polymers FcCuCN and FcAgCN possess nearly similar band gaps, while the band gap of FcCuI is relatively broader.